Fundus Autofluorescence Imaging in Age-Related Macular Degeneration. (January 2015) - Batıoğlu, Figen; Demirel, Sibel; Özmert, Emin
Abstract Fundus autofluorescence (FAF) is a noninvasive imaging technology that provides information on the distribution of lipofuscin within the retinal pigment epithelial cells. Progressive accumulation of lipofuscin within retinal pigment epithelial cells is involved in the pathogenesis of age-related macular degeneration (AMD). Fundus autofluorescence imaging using a confocal scanning laser ophthalmoscope is a useful technique to identify high-risk characteristics in patients with nonexudative AMD. It gives also some valuable knowledge and clues in differantial diagnosis of exudative age-related macular degeneration. This review comprises an introduction to fundus autofluorescence, a review of FAF imaging in AMD, and the recent classification of geographic atrophy (GA) and early AMD phenotypes by the Fundus Autofluorescence in Age-related Macular Degeneration Study. The association of phenotype and atrophy progression and choroidal neovascularization development are also summarized.